Factors governing the solid phase distribution of Cr, Cu and As in contaminated soil after 40 years of ageing - Tardif, Stacie; Cipullo, Sabrina; Sø, Helle U.; Wragg, Joanna; Holm, Peter E.; Coulon, Frederic; Brandt, Kristian K.; Cave, Mark (Elsevier, 2018)
The physico-chemical factors affecting the distribution, behavior and speciation of chromium (Cr), copper (Cu) and arsenic (As) was investigated at a former wood impregnation site (Fredensborg, Denmark). Forty soil samples were collected and extracted using a sequential extraction technique known as the Chemometric Identification of Substrates and Element Distributions (CISED) and a multivariate statistical tool (redundancy analysis) was applied. CISED data was linked to water-extractable Cr, Cu and As and bioavailable Cu as determined by a whole-cell bacterial bioreporter assay. Results showed that soil pH significantly affected the solid phase distribution of all three elements on site. Additionally, elements competing for binding sites, Ca, Mg and Mn in the case of Cu, and P, in the case of As, played a major role in the distribution of these elements in soil. Element-specific distributions were observed amongst the six identified soil phases including residual pore salts, exchangeable, carbonates (tentative designation), Mn-Al oxide, amorphous Fe oxide, and crystalline Fe oxide. While Cr was strongly bound to non-extractable crystalline Fe oxide in the oxic top soil, Cu and notably, As were associated with readily extractable phases, suggesting that Cu and As, and not Cr, constitute the highest risk to environmental and human health. However, bioavailable Cu did not significantly correlate with CISED identified soil phases, suggesting that sequential extraction schemes such as CISED may not be ideally suited for inferring bioavailability to microorganisms in soil and supports the integration of receptor-specific bioavailability tests into risk assessments as a complement to chemical methods.
Keywords: Contaminated soil; Sequential extraction; Bioavailability; Metal speciation; Chromated copper arsenate; Chemometrics